Neurologic and radiographic findings associated with paediatric inflammatory multisystem syndrome temporally associated with SARS-CoV-2 (PIMS-TS). Issue 6 (27th May 2022) - Abdel-Mannan, Omar; Penner, Justin; Hassell, Jane; Loebel, Ulrike; Maillard, Sue; Johnson, Mae; Pressler, Ronit; Bamford, Alasdair; Moshal, Karyn; Hacohen, Yael
Abstract : Objective: Our aim was to report neurological manifestations of children with paediatric inflammatory multisystem syndrome temporally associated with SARS-CoV-2 (PIMS-TS). Methods: Patients (<18yrs) presenting to Great Ormond Street Hospital between March 1, 2020, and June 21, 2020 fulfilling RCPCH PIMS-TS criteria, were included. Clinical and paraclinical features were retrieved retrospectively from electronic patient records. Results: New-onset neurological symptoms/signs were reported in 23/45 (51.1%); headaches (n=16), encephalopathy (n=7), dysarthria/dysphonia (n=6), hallucinations (n=4), ataxia (n=4), peripheral nerve involvement (n=3), and seizures (n=1). Five (21.7%) patients had CSF analysis; 1 patient had 118 leuko- cytes in CSF. Splenium signal changes were seen in 4/14 patients who had brain MRI. A mild excess of slow activity was found in 10/10 who had an EEG and mild myopathic and neuropathic changes were seen 4/5 who underwent nerve conduction studies and electromyography. Children with neurological involvement had higher peak inflammatory markers and were more likely to be ventilated and require inotropic support in PICU (p<0.05). Conclusions: Children with PIMS-TS presented with new neurological symptoms involving both the central and peripheral nervous systems, in the absence of respiratory symptoms. Neurological symptoms were seen more frequently in more severe presentations. o.abdel-mannan@ucl.ac.uk